2018
DOI: 10.1016/j.ultsonch.2017.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Isotherms and kinetic study of ultrasound-assisted adsorption of malachite green and Pb2+ ions from aqueous samples by copper sulfide nanorods loaded on activated carbon: Experimental design optimization

Abstract: Copper sulfide nanorods loaded on activated carbon (CuS-NRs-AC) was synthesized and used for simultaneous ultrasound-assisted adsorption of malachite green (MG) and Pb ions from aqueous solution. Following characterization of CuS-NRs-AC were investigated by SEM, EDX, TEM and XRD, the effects of pH (2.0-10), amount of adsorbent (0.003-0.011g), MG concentration (5-25mgL), Pb concentration (3-15mgL) and sonication time (1.5-7.5min) and their interactions on responses were investigated by central composite design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(41 citation statements)
references
References 59 publications
1
38
0
1
Order By: Relevance
“…A comparison study was made between the results achieved in this work through 10 wt% SA@HKUST-1 with those obtained by other adsorbents reported previously in the literature e.g. Bentonite, 72 CNF aerogel, 73 almond gum, 74 CuS-NRs-AC, 75 ZnS:Cu-NP-AC, 76 CO 2 -activated carbon (CAC). 77 The results demonstrated that SA@HKUST-1 among other various adsorbents mentioned above and reported at Table 6S, † behaves as an effective adsorbent for adsorption of MG dye and Pb(II) with respect to maximum adsorption capacity (mg g À1 ).…”
Section: Adsorption Isothermsmentioning
confidence: 72%
“…A comparison study was made between the results achieved in this work through 10 wt% SA@HKUST-1 with those obtained by other adsorbents reported previously in the literature e.g. Bentonite, 72 CNF aerogel, 73 almond gum, 74 CuS-NRs-AC, 75 ZnS:Cu-NP-AC, 76 CO 2 -activated carbon (CAC). 77 The results demonstrated that SA@HKUST-1 among other various adsorbents mentioned above and reported at Table 6S, † behaves as an effective adsorbent for adsorption of MG dye and Pb(II) with respect to maximum adsorption capacity (mg g À1 ).…”
Section: Adsorption Isothermsmentioning
confidence: 72%
“…The CuS‐NPs were synthesized based on the reaction of the mixture of copper acetate (Cu (CH 3 COO) 2 .H 2 O) with thioacetamide (CH 3 CSNH 2 ) in aqueous media. In a typical synthesis, 10 ml of 0.1 mol L −1 copper acetate solution and 20 ml of 0.2 mol L −1 tri‐sodium citrate solution as capping agent were taken into a 100 ml beaker. In the next step, 5 ml of 0.4 mol L −1 thioacetamide (TAA) as source for S 2− ions was slowly added to the solution.…”
Section: Methodsmentioning
confidence: 99%
“…Here, C t /C 0 versus time provided the slopes of the curves derived from Eq. 4 Here, C t and C 0 denote the initial concentrations of Pb 2+ at time t, S s equals the exposed specific surface area of the adsorbent, and Kf denotes the coefficient of mass transfer (Sharifpour et al 2018). These models as reviewed by Qiu et al (2009) and derived from the Freundlich isotherm were adopted to describe sorption of Pb 2+ ions.…”
Section: Batch Mode Adsorption Experimentsmentioning
confidence: 99%